Shifting the narrative: equity, evidence, effectiveness, and innovation in the era of Ending the HIV Epidemic - Alexander Perez; Rosy Galván; Milanes Morejon (BMC, 2022)
Abstract Background The use of evidence-based (EB) and evidence-informed (EI) criteria in determining the effectiveness of health interventions has been widely adopted by national and international agencies in their attempt to address health gaps, particularly around Ending the HIV Epidemic (EHE) initiatives. Utilization of these rigorous standards has proven critical in making progress towards achieving EHE goals, yet many communities remain unreached and underserved despite widespread adoption of EB/EI standards in public health research and practice. Although a crucial tool for innovative healthcare delivery, emphasis on the use of EB/EI parameters has created bias within the cycle of knowledge creation that favors well-resourced institutions given their capacity to meet the rigorous evaluation standards required of EB/EI science. This bias can systematically exclude institutions more aligned with community needs, such as community-based organizations and other grass-roots initiatives, which may have long-standing interventions that more effectively engage marginalized groups but do not have the capacity to meet EB/EI standards. Main body This paper will explore the manifestation of systematic bias and research inequity in the process of identifying and assessing EB/EI HIV care interventions through the lens of a Health Resources and Services Administration funded initiative, coined the Center for Innovation and Engagement, which supports people living with HIV in the United States. An overview of the initiative is provided along with examples of how promising interventions with positive outcomes for members of marginalized communities are excluded in place of interventions that meet traditional standards of scientific rigor but are not novel or particularly innovative. Themes around academic imperialism and power hierarchies will be considered along with key barriers, lessons learned, and recommendations for promoting more equitable EB/EI research practice. Conclusions It is crucial for entities supporting public health interventions to prioritize equity and inclusion in all stages of funding, design, and implementation. This is particularly true for conditions, such as HIV, that disproportionally impact the most marginalized. This will require approaching EB/EI research with a critical lens towards power and a willingness to dismantle historical dynamics that perpetuate inequities as a way of encouraging truly innovative solutions to support those who need it most.